Soil fauna modulates the effect of experimental drought on litter decomposition in forests invaded by an exotic pathogen. (1st July 2021) - Homet, Pablo; Gómez‐Aparicio, Lorena; Matías, Luis; Godoy, Oscar
Abstract: Litter decomposition is a fundamental process for nutrient cycling and C fluxes between terrestrial ecosystems and the atmosphere. Multiple factors such as environmental conditions, litter quality and decomposer organisms are known to influence this ecological process in direct and indirect ways. However, it remains poorly understood to what extent this entangled bank of complex interactions can be disrupted by several global change drivers such as climate change and invasive species. Here we reported main findings from a litter decomposition experiment conducted in a natural mixed forest invaded by Phytophthora cinnamomi, an exotic oomycete well known for causing tree disease and forest decline. In two Mediterranean forest types (namely woodland and closed forest), we first built a rainfall exclusion infrastructure to reduce natural precipitation by 30%. Then, we followed the spatial variation in C and N leaf litter dynamics as well as the abundance of the exotic oomycete P . cinnamomi for 18 months under both control and rainfall exclusion conditions using a litter bag methodology with different mesh sizes to further evaluate the indirect role of mesofauna abundance and diversity in litter C and N temporal dynamics. Significant reductions in soil moisture produced by the experimental rainfall exclusion increased C litter loss with time directly, and indirectly via increases in overall mesofauna abundance and changes in the ratio between predators and decomposers. N litter dynamics were in contrast modulated mainly by initial litter quality. Surprisingly, P. cinnamomi abundance did not correlate with variation in initial litter quality as previously suggested, but we found that the exotic oomycete was negatively correlated with both decomposer and predator abundances. These results suggest it might participate indirectly in litter decomposition dynamics through the biotic soil component. Synthesis . Contrary to expected, our results show that a moderate but realistic rainfall reduction can accelerate the litter decomposition process. It also points out to litter fauna as a key component modulating the indirect impacts of global change drivers on litter decomposition. Abstract : Contrary to expected, our results show that a moderate but realistic rainfall reduction can accelerate the litter decomposition process. It also points out to litter fauna as a key component modulating the indirect impacts of global change drivers on litter decomposition. Resumen: La descomposición de la hojarasca es un proceso fundamental para el ciclo de nutrientes y los flujos de C entre los ecosistemas terrestres y la atmósfera. Se sabe que en este proceso ecológico influyen directa e indirectamente múltiples factores que interaccionan entre sí, como las condiciones ambientales, la calidad de la hojarasca y los organismos descomponedores. Sin embargo, se desconoce hasta qué punto este intrincado conjunto de interacciones complejas puede verse afectado por diversos factores del cambio global, como el cambio climático y las especies invasoras. En este estudio presentamos los principales hallazgos de un experimento de descomposición de hojarasca realizado en dos bosques mixtos mediterráneos invadidos por Phytophthora cinnamomi, un oomiceto exótico conocido por causar enfermedades de los árboles y decaimiento forestal. En primer lugar, construimos una infraestructura de exclusión de lluvia para reducir las precipitaciones naturales en un 30% en dos tipos de bosque. A continuación, estudiamos la variación en el contenido de C y N de la hojarasca, así como la abundancia de P. cinnamomi durante 18 meses bajo condiciones de control y exclusión de lluvia. Utilizamos bolsas de hojarasca con diferentes tamaños de malla para evaluar en profundidad el papel de la abundancia y diversidad de la mesofauna en la dinámica temporal del C y N de la hojarasca. La reducción significativa de la humedad del suelo producida por la exclusión experimental de lluvia afectó directamente incrementando la pérdida de C de la hojarasca con el tiempo, e indirectamente a través de un aumento en la abundancia general de la mesofauna y cambios en la proporción entre depredadores y descomponedores. Por el contrario, la dinámica del N fue modulada principalmente por la calidad inicial de la hojarasca. Sorprendentemente, la abundancia de P. cinnamomi no se correlacionó con la variación en la calidad inicial de la hojarasca, aunque el oomiceto exótico se correlacionó negativamente con la abundancia de descomponedores y depredadores. Estos resultados sugieren que P. cinnamomi podría participar indirectamente en la dinámica de descomposición de la hojarasca con efectos sobre el componente biótico del suelo. Síntesis . Al contrario de lo esperado, nuestros resultados muestran que una reducción moderada de las precipitaciones puede acelerar el proceso de descomposición de la hojarasca. También señalan a la mesofauna como un componente clave que modula los impactos indirectos de los motores del cambio global en la descomposición de la hojarasca.